Geo-mapping of hazards, risks, and travel health services in Bali: Results from the first stage of the integrated travel health surveillance and information system at destination (TravHeSID) project. Issue 37 (September 2020) - Wirawan, I Md Ady; Putri, Wayan Citra Wulan Sucipta; Kurniasari, Ni Made Dian; Mulyawan, Ketut Hari; Hendrayana, Made Agus; Suharlim, Christian
Abstract: Background: Currently, the main travel health surveillance system relies on ill-returned travelers data and has been mainly designed for countries of origin in developed regions. This study aims to develop an integrated travel health surveillance and information system for destination sites in Bali. Methods: The first stage of the project included mapping and geo-tagging of health hazards and risks as well as travel health facilities, involving 197 tourist attractions in 8 regencies and 1 city in Bali. Hazard identifications were performed and risk levels were assessed using a qualitative risk assessment matrix. Results: Health and safety hazards, risk levels, and travel health services with their geographical positions were mapped. Based on types of tourist attractions, 59 (29.9%) were beaches, 28 (14.2%) were temples, and 25 (12.7%) were waterfalls. Of the 197 tourist attractions, 107 (54.3%) were categorized as low-risk areas, 77 (39.1%) medium-risk areas, and 13 (6.6%) high-risk areas. The most common hazards included lack of proper access, risks of slips, trips, and falls, risks posed by water-based activities, mosquitoes as vectors of diseases, risks of bites or scratches from rabid animal, mixed brews containing methanol, and hyperbaric condition in diving sites. Conclusions: The opportunity of providing site-specific preventive measures to travelers was highlighted in this study.